Social work perplexity: Dissonance, uncertainty, and growth in Kazakhstan. (March 2019) - Chappell Deckert, Jennifer; Koenig, Terry L
Social work pioneer Jane Addams wrote of her experiences living and working with immigrant populations at the Hull-House in Chicago. In her writings, she describes a state of perplexity in which her personal and professional assumptions about the world were transformed through her interactions with that community. Perplexity is a liminal or in-between state of being in professional social work practice settings, which encourages the recognition of uncertainty, honors the dissonance between past assumptions and new understandings, and creates opportunities for meaningful relationships, personal growth, and social reform. This approach employs methods of mutual transformation through individual interpretations of experience, and holistic, critical practice. Our article argues that perplexity offers a useful alternative to social work approaches primarily based in mastery and expertise and is a good fit for the complex and diverse practice situations common to social work. By providing opportunities for truly collaborative understanding, engaging perplexity in social work is an innovative alternative to more linear, cause-and-effect thinking in the field. Specific elements of perplexity are discussed and paired with a case example from social work practice in Kazakhstan with implications for social work practice in other contexts.